A wear-resistant and waterproof epoxy anticorrosive coating and preparation method thereof
By grafting carboxyphthalene on nylon fibers, a cross-linking network with epoxy resin is formed, which solves the problem of poor compatibility between nylon fiber and epoxy resin, and significantly improves the wear resistance and water resistance of epoxy resin. and thermal stability properties.
Patent Information
- Application Number
- CN202410514277.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-26
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-04-26
AI Technical Summary
The nylon fiber has poor compatibility with epoxy resin, resulting in insufficient waterproof, thermal stability and wear resistance of epoxy resin.
Carboxyphthalene grafted nylon fiber is combined with epoxy resin, and carboxy and phthalene groups are introduced on the surface of the nylon fiber by irradiation grafting to form a cross-linking network, enhancing interface strength and improving waterproofing and Thermal stability.
It significantly improves the wear resistance, impact strength and tensile properties of epoxy resin, reduces water absorption, and improves the thermal decomposition temperature and waterproof performance.
Smart Images

Figure BDA0004812905770000051 
Figure BDA0004812905770000052 
Figure BDA0004812905770000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, in particular to a wear-resistant and waterproof epoxy anticorrosive coating and a preparation method thereof. Background Art
[0002] Epoxy resin coating has excellent anti-corrosion performance, dielectric properties and chemical stability, and is widely used in various fields of industrial production and daily life. At present, toughening and modifying epoxy resin to improve its toughness, impact resistance, waterproofness, wear resistance and other properties is a research hotspot. Commonly used epoxy resin modifiers mainly include nitrile rubber, phenolic resin, phthalonitrile resin, etc. Among them, phthalonitrile resin can undergo addition polymerization at high temperature to generate a thermally stable nitrogen heterocyclic structure, which has excellent thermal oxidation stability and structural stability, and has broad application prospects in epoxy resin. Nylon fiber has strong wear resistance, rebound performance and mechanical strength, and is widely used in materials such as epoxy resin. However, nylon fiber has poor compatibility with epoxy resin, and simple physical blending will cause phase separation between nylon fiber and epoxy resin, affecting the mechanical properties of epoxy resin. Patent CN104830028B discloses that nylon 6 fiber is modified; then blended with epoxy resin, there is good interface bonding strength and excellent mechanical properties. However, this patent does not improve the waterproof, thermal stability and wear resistance of epoxy resin. Summary of the invention
[0003] The technical problem solved by the invention is: the epoxy resin coating is toughened and modified by using carboxyl phthalonitrile grafted nylon fiber, thereby improving the waterproof, thermal stability and wear resistance of the epoxy coating.
[0004] The technical solution provided by the present invention is:
[0005] A wear-resistant and waterproof epoxy anticorrosive coating comprises the following components in parts by weight: 100 parts of epoxy resin, 1-15 parts of carboxyl phthalonitrile grafted nylon fiber, 6-9 parts of imidazole curing agent, 0.5-1 part of defoaming agent, and 0.2-0.6 part of leveling agent.
[0006] The preparation method of carboxyphthalonitrile grafted nylon fiber is as follows: add 4,5-di(enylcysteine)phthalonitrile to water, stir and prepare a pre-grafting solution with a mass concentration of 20-70g / L; then add nylon 6 fiber, mix well and place in the irradiation tube of the electron irradiation equipment, introduce nitrogen, and 60 A Coγ-ray source is used as an irradiation source to perform irradiation grafting, and the fiber is taken out, placed in xylene, stirred, filtered, washed with ethanol, and dried to obtain carboxyphthalonitrile grafted nylon fiber.
[0007] Among them, the imidazole curing agent includes 2-methylimidazole, 2-ethyl-4-methylimidazole, and 2-undecylimidazole.
[0008] The absorbed dose of the irradiation grafting is 15-150 kGy, and the irradiation grafting time is 6-12 hours.
[0009] Wherein, the preparation method of 4,5-di(alkenylcysteine)phthalonitrile is as follows:
[0010] (1) Add 4,5-dichlorophthalonitrile, Boc-cysteine and potassium carbonate to N,N-dimethylformamide, raise the temperature to 70-85°C in a nitrogen atmosphere, stir and react for 6-18 hours, add water and dichloromethane, extract and dry the organic layer, concentrate, dissolve the product in dichloromethane, add trifluoroacetic acid, stir and react at room temperature for 3-5 hours, concentrate to remove dichloromethane and trifluoroacetic acid, and purify by recrystallization from ethyl acetate to obtain intermediate A.
[0011] (2) Add acryloyl chloride, intermediate A, and N,N-diisopropylethylamine in a ratio of (1.8-2.2) mol:1 mol:(2-2.3) mol to tetrahydrofuran, react at room temperature for 3-8 hours, concentrate to remove tetrahydrofuran, and purify by recrystallization from ethyl acetate to obtain 4,5-di(enylcysteine)phthalonitrile.
[0012] Among them, the ratio of 4,5-dichlorophthalonitrile, Boc-cysteine and potassium carbonate in (1) is 1 mol:(4-4.8) mol:(3-4.2) mol.
[0013] Among them, the preparation method of the wear-resistant and waterproof epoxy anti-corrosion coating is as follows: 1-15 parts of carboxyl phthalonitrile grafted nylon fiber are added to 100 parts of epoxy resin, ultrasonically dispersed, and then 0.5-1 parts of defoaming agent, 0.2-0.6 parts of leveling agent, and 6-9 parts of imidazole curing agent are added, and mixed to obtain the wear-resistant and waterproof epoxy anti-corrosion coating; the curing process of the wear-resistant and waterproof epoxy anti-corrosion coating is: 120℃ / 1h, 180℃ / 2h, 200℃ / 2h, 220℃ / 3h, 250℃ / 3h; and the epoxy resin cured product is obtained.
[0014] The technical effect of the invention is that the invention utilizes 4,5-dichlorophthalonitrile, Boc-cysteine, acryloyl chloride and the like as reaction agents to prepare a 4,5-di(alkenylcysteine)phthalonitrile functional monomer, which contains a plurality of hydrophilic carboxyl groups and amide bonds, has good solubility in water, and can be configured into a uniform pre-grafting solution, thus providing convenience for subsequent irradiation grafting reactions.
[0015] The present invention adopts the radiation grafting method, utilizes 4,5-di(enylcysteine)phthalonitrile to irradiate graft nylon 6 fiber, realizes the introduction of carboxyl, phthalonitrile and other groups on the surface of nylon 6 fiber, obtains carboxyl phthalonitrile grafted nylon fiber, and is compounded with epoxy resin as a filler. During the thermal curing process, the carboxyl of nylon fiber and epoxy resin are cross-linked and cured, and the interface strength between nylon fiber and epoxy resin is enhanced, and the wear resistance, impact strength and tensile properties of epoxy resin are significantly improved. Nylon fiber forms a tight three-dimensional cured cross-linked network in epoxy resin, which can inhibit water molecules from entering the epoxy resin matrix, is conducive to reducing water absorption, and improves waterproof performance.
[0016] During the thermal curing process, the phthalonitrile on the surface of the nylon fiber generates thermally stable nitrogen heterocyclic structures such as triazine at high temperatures, which have excellent thermal oxidation stability and structural stability, increase the thermal decomposition temperature of the epoxy resin, and show better heat resistance. DETAILED DESCRIPTION
[0017] The content of the present invention is further described below in conjunction with specific examples, but it should not be construed as limiting the present invention. If not specifically indicated, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0018] In the present invention, the CAS number of 4,5-dichlorophthalonitrile is 139152-08-2, the CAS number of Boc-cysteine is 149270-12-2, the epoxy resin model is E44, the defoamer brand is BYK-A350, and the leveling agent brand is BYK-310 of 2-6g.
[0019] Example 1
[0020] (1) 2 mmol 4,5-dichlorophthalonitrile, 9.6 mmol Boc-cysteine and 6 mmol potassium carbonate were added to 20 mL N,N-dimethylformamide, heated to 70°C in a nitrogen atmosphere, stirred and reacted for 12 h, water and dichloromethane were added, the organic layer was dried and concentrated after extraction, the product was dissolved in dichloromethane, trifluoroacetic acid was added, stirred and reacted at room temperature for 5 h, concentrated to remove dichloromethane and trifluoroacetic acid, and purified by recrystallization from ethyl acetate to obtain intermediate A.
[0021] (2) 5.4 mmol acryloyl chloride, 3 mmol intermediate A, and 6.9 mmol N,N-diisopropylethylamine were added to 25 mL tetrahydrofuran, and the mixture was reacted at room temperature for 5 h. The tetrahydrofuran was removed by concentration, and the mixture was purified by recrystallization from ethyl acetate to obtain 4,5-di(enylcysteine)phthalonitrile.
[0022] (3) Add 4,5-di(enylcysteine)phthalonitrile to water and stir to prepare a pre-grafting solution with a mass concentration of 20 g / L; then add nylon 6 fiber, mix well and place in the irradiation tube of the electron irradiation equipment, and introduce nitrogen to 60 A Coγ-ray source was used as the irradiation source, and the absorbed dose was controlled to be 15 kGy. The irradiation grafting was performed for 12 hours. The fiber was taken out, placed in xylene, filtered after stirring, washed with ethanol, and dried to obtain carboxyphthalonitrile grafted nylon fiber.
[0023] (4) Add 10 g of carboxyl phthalonitrile grafted nylon fiber to 1000 g of epoxy resin, disperse it by ultrasonication, then add 5 g of defoamer, 2 g of leveling agent, and 78 g of 2-ethyl-4-methylimidazole curing agent, mix well to obtain a wear-resistant and waterproof epoxy anti-corrosion coating; the curing process is: 120°C / 1h, 180°C / 2h, 200°C / 2h, 220°C / 3h, 250°C / 3h; and obtain an epoxy resin cured product.
[0024] Example 2
[0025] (1) 2 mmol 4,5-dichlorophthalonitrile, 8.9 mmol Boc-cysteine, and 7.6 mmol potassium carbonate were added to 20 mL N,N-dimethylformamide, heated to 85°C in a nitrogen atmosphere, stirred and reacted for 6 h, water and dichloromethane were added, the organic layer was dried and concentrated after extraction, the product was dissolved in dichloromethane, trifluoroacetic acid was added, stirred and reacted at room temperature for 3 h, concentrated to remove dichloromethane and trifluoroacetic acid, and purified by recrystallization from ethyl acetate to obtain intermediate A. The preparation reaction route is as follows:
[0026]
[0027] (2) Add 6.6 mmol acryloyl chloride, 3 mmol intermediate A, and 6 mmol N,N-diisopropylethylamine to 30 mL tetrahydrofuran, react at room temperature for 8 hours, concentrate to remove tetrahydrofuran, and purify by recrystallization from ethyl acetate to obtain 4,5-di(enylcysteine)phthalonitrile. The preparation reaction route is as follows:
[0028]
[0029] (3) Add 4,5-di(enylcysteine)phthalonitrile to water, stir and prepare a pre-grafting solution with a mass concentration of 50 g / L; then add nylon 6 fiber, mix well and place in the irradiation tube of the electron irradiation equipment, introduce nitrogen gas, and 60A Coγ-ray source was used as the irradiation source, and the absorbed dose was controlled to be 150 kGy. The irradiation grafting was performed for 6 hours. The fiber was taken out, placed in xylene, filtered after stirring, washed with ethanol, and dried to obtain carboxyphthalonitrile grafted nylon fiber.
[0030] (4) Add 80g of carboxylphthalonitrile grafted nylon fiber to 1000g of epoxy resin, disperse it by ultrasonic, then add 8g of defoamer, 6g of leveling agent, and 60g of 2-methylimidazole curing agent, mix well to obtain a wear-resistant and waterproof epoxy anti-corrosion coating; the curing process is: 120℃ / 1h, 180℃ / 2h, 200℃ / 2h, 220℃ / 3h, 250℃ / 3h; and obtain epoxy resin cured product.
[0031] Example 3
[0032] (1) 2 mmol 4,5-dichlorophthalonitrile, 8 mmol Boc-cysteine, and 8.4 mmol potassium carbonate were added to 20 mL N,N-dimethylformamide, heated to 70°C in a nitrogen atmosphere, stirred and reacted for 18 h, water and dichloromethane were added, the organic layer was dried and concentrated after extraction, the product was dissolved in dichloromethane, trifluoroacetic acid was added, stirred and reacted at room temperature for 3 h, concentrated to remove dichloromethane and trifluoroacetic acid, and purified by recrystallization from ethyl acetate to obtain intermediate A.
[0033] (2) 6.6 mmol acryloyl chloride, 3 mmol intermediate A, and 6.9 mmol N,N-diisopropylethylamine were added to 30 mL tetrahydrofuran, and the mixture was reacted at room temperature for 3 h. The tetrahydrofuran was removed by concentration, and the mixture was purified by recrystallization from ethyl acetate to obtain 4,5-di(enylcysteine)phthalonitrile.
[0034] (3) Add 4,5-di(enylcysteine)phthalonitrile to water and stir to prepare a pre-grafting solution with a mass concentration of 70 g / L; then add nylon 6 fiber, mix well and place in the irradiation tube of the electron irradiation equipment, and introduce nitrogen to 60 A Coγ-ray source was used as the irradiation source, and the absorbed dose was controlled to be 100 kGy. The irradiation grafting was performed for 12 hours. The fiber was taken out, placed in xylene, filtered after stirring, washed with ethanol, and dried to obtain carboxyphthalonitrile grafted nylon fiber.
[0035] (4) Add 150g of carboxylphthalonitrile grafted nylon fiber to 1000g of epoxy resin, disperse it by ultrasonication, then add 10g of defoamer, 6g of leveling agent, and 90g of 2-undecyl imidazole curing agent, mix well to obtain a wear-resistant and waterproof epoxy anti-corrosion coating; the curing process is: 120℃ / 1h, 180℃ / 2h, 200℃ / 2h, 220℃ / 3h, 250℃ / 3h; and obtain epoxy resin cured product.
[0036] Comparative Example 1
[0037] Add 5 g of defoamer, 2 g of leveling agent and 78 g of 2-ethyl-4-methylimidazole curing agent to 1000 g of epoxy resin, mix well to obtain epoxy coating; the curing process is: 120°C / 1h, 180°C / 2h, 200°C / 2h, 220°C / 3h, 250°C / 3h; and obtain epoxy resin cured product.
[0038] Comparative Example 2
[0039] 10g of nylon 6 fiber was added to 1000g of epoxy resin, and the mixture was dispersed by ultrasonication. Then, 5g of defoamer, 2g of leveling agent, and 78g of 2-ethyl-4-methylimidazole curing agent were added and mixed to obtain epoxy coating. The curing process was as follows: 120℃ / 1h, 180℃ / 2h, 200℃ / 2h, 220℃ / 3h, and 250℃ / 3h. The epoxy resin cured product was obtained.
[0040] Comparative Example 3
[0041] 10 g of 4,5-di(enylcysteine)phthalonitrile was added to 1000 g of epoxy resin, and the mixture was dispersed by ultrasonication. Then, 5 g of defoamer, 2 g of leveling agent, and 78 g of 2-ethyl-4-methylimidazole curing agent were added and mixed to obtain epoxy coating. The curing process was as follows: 120°C / 1 h, 180°C / 2 h, 200°C / 2 h, 220°C / 3 h, and 250°C / 3 h. The epoxy resin cured product was obtained.
[0042] The thermal properties of epoxy resin cured product were tested by thermogravimetric analyzer with nitrogen loss of 100 mL / min, heating rate of 10 °C / min and maximum test temperature of 800 °C.
[0043] Waterproof performance test of epoxy resin cured product: Weigh a certain mass (m0) of epoxy resin cured product, soak it in 80℃ water for 72h, take out the epoxy resin cured product, absorb the surface moisture with filter paper, weigh it (m1), and calculate the water absorption rate W, W = (m1-m0) / m0×100%. The lower the water absorption rate, the better the waterproof performance.
[0044] Table 1 Epoxy resin performance test
[0045]
[0046] The friction performance of epoxy resin cured material was tested by friction and wear testing machine. The friction part was 45# steel ring and the load value was 19.6N. The speed was 300r / min. The weight of epoxy resin cured material before and after friction was weighed as M0 and M1 respectively. The width L of epoxy resin cured material and the width D of wear scar were measured. The mass loss rate S per unit area was calculated; S = (M0-M1) / (L×D). The smaller the mass loss rate S, the better the wear resistance.
[0047] The tensile properties of epoxy resin cured products were tested according to GB / T 1040.1-2006 method.
[0048] The impact properties of epoxy resin cured products were tested according to GB / T 1843-2008 method.
[0049]
[0050] Each embodiment uses carboxyl phthalonitrile grafted nylon fiber as a filler and is compounded with epoxy resin. During the thermal curing process, the carboxyl group of the nylon fiber and the epoxy resin are cross-linked and cured, which enhances the interface strength between the nylon fiber and the epoxy resin and significantly improves the wear resistance, impact strength and tensile properties of the epoxy resin. The nylon fiber forms a tight three-dimensional cured cross-linked network in the epoxy resin, which can inhibit water molecules from entering the epoxy resin matrix, which is beneficial to reducing water absorption and improving waterproof performance.
[0051] During the thermal curing process, the phthalonitrile on the surface of the nylon fiber generates thermally stable nitrogen heterocyclic structures such as triazine at high temperatures, which have excellent thermal oxidation stability and structural stability, increase the thermal decomposition temperature of the epoxy resin, and show better heat resistance.
[0052] In Comparative Example 1, no carboxyl phthalonitrile grafted nylon fiber was added, the water absorption rate of the epoxy resin was high, the thermal decomposition temperature was high, and the wear resistance and tensile properties were poor.
[0053] In Comparative Example 2, only ordinary nylon 6 fiber is added, which does not contain carboxyl groups and cannot undergo a curing reaction with the epoxy resin. The two have poor compatibility, low interface bonding strength, and poor wear resistance and tensile properties of the epoxy resin.
[0054] In Comparative Example 3, only 4,5-di(enylcysteine)phthalonitrile was added without adding nylon fiber, which had no effect on improving the wear resistance and tensile properties of the epoxy resin.
[0055] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A wear-resistant and waterproof epoxy anticorrosive coating, characterized in that: The invention comprises the following components in parts by weight: 100 parts of epoxy resin, 1-15 parts of carboxyl phthalonitrile grafted nylon fiber, 6-9 parts of imidazole curing agent, 0.5-1 parts of defoaming agent, and 0.2-0.6 parts of leveling agent; The preparation method of the carboxyl phthalonitrile grafted nylon fiber is as follows: 4,5-di(enylcysteine)phthalonitrile is added to water, and the solution is prepared after stirring to form a pre-grafting solution; then nylon 6 fiber is added, mixed and placed in an irradiation tube of an electron irradiation device, and nitrogen is introduced to form a pre-grafting solution; 60 A Coγ-ray source is used as an irradiation source to perform irradiation grafting, and the fiber is taken out, placed in xylene, stirred, filtered, washed, and dried to obtain carboxyphthalonitrile grafted nylon fiber; The preparation method of the 4,5-di(alkenylcysteine)phthalonitrile is as follows: (1) Add 4,5-dichlorophthalonitrile, Boc-cysteine and potassium carbonate to N,N-dimethylformamide, raise the temperature to 70-85°C in a nitrogen atmosphere, stir and react for 6-18 hours, dissolve the extracted product in dichloromethane, add trifluoroacetic acid, stir and react at room temperature for 3-5 hours, and purify by recrystallization to obtain intermediate A; (2) adding acryloyl chloride, intermediate A, and N,N-diisopropylethylamine to tetrahydrofuran, reacting at room temperature for 3-8 hours, and purifying by recrystallization to obtain 4,5-di(enylcysteine)phthalonitrile; The ratio of 4,5-dichlorophthalonitrile, Boc-cysteine and potassium carbonate in (1) is 1 mol: (4-4.8) mol: (3-4.2) mol; The ratio of acryloyl chloride, intermediate A and N,N-diisopropylethylamine in (2) is (1.8-2.2) mol:1 mol:(2-2.3) mol.
2. The wear-resistant and waterproof epoxy anticorrosive coating according to claim 1, characterized in that: The imidazole curing agent includes 2-methylimidazole, 2-ethyl-4-methylimidazole, and 2-undecylimidazole.
3. The wear-resistant and waterproof epoxy anticorrosive coating according to claim 1, characterized in that: The mass concentration of the pre-grafting solution is 20-70 g / L.
4. The wear-resistant and waterproof epoxy anticorrosive coating according to claim 1, characterized in that: The absorbed dose of the radiation grafting is 15-150 kGy, and the radiation grafting time is 6-12 hours.
5. A method for preparing the wear-resistant and waterproof epoxy anticorrosive coating according to any one of claims 1 to 4, characterized in that: 1-15 parts of carboxyl phthalonitrile grafted nylon fiber are added to 100 parts of epoxy resin, dispersed by ultrasonication, and then 0.5-1 parts of defoamer, 0.2-0.6 parts of leveling agent and 6-9 parts of imidazole curing agent are added and mixed to obtain a wear-resistant and waterproof epoxy anticorrosive coating.
6. A curing process for the wear-resistant and waterproof epoxy anticorrosive coating obtained by the preparation method according to claim 5, characterized in that: The curing process of the wear-resistant and waterproof epoxy anti-corrosion coating is as follows: 120℃ / 1h, 180℃ / 2h, 200℃ / 2h, 220℃ / 3h, and 250℃ / 3h.
